Experimental and Numerical Simulation Study of Ultrasonic Vibration Effect on Abrasive Grain Distribution and Movement Behavior in Laser Cladding Melt Pool for Abrasive Layer Fabrication - Zixuan Wang; Ying Chen; Chuang Guan; Jiahui Du; Tianbiao Yu; Ji Zhao; Jun Zhao (Applied Sciences)
The ultrasonic vibration laser cladding method is a material-saving and green method to fabricate super abrasive structured grinding wheels. However, the mechanism of the ultrasonic vibration’s effect on the movement behavior of abrasive grains in the laser cladding process has not been clarified. To address this, the impacts of ultrasonic vibration on the abrasive grain distribution and movement behavior were experimentally studied, and the numerical simulation method was introduced to simulate the ultrasonic vibration laser cladding process. A two-dimensional Gaussian cross-section heat source model was developed, and its energy density conformed to a Gaussian distribution in both space and time. The simulations of the temperature and fluid fields of the melt pool were carried out. The CBN abrasive grains in the melt pool were subjected to gravity, the buoyancy force, the drag force of the metal fluid, and the sonophoretic radiation force of the ultrasonic vibration. Based on them, the effects of ultrasonic vibration on the movement behaviors and trajectories of the CBN abrasive grains were analyzed. The influence of the ultrasonic amplitude on the distribution of abrasive grains was studied. The simulation results revealed that the abrasive grains could be uniformly distributed on the surface of the cladding layer during the ultrasonic vibration laser cladding process.